2003
DOI: 10.1139/z02-242
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of predators on endangered species using a bioenergetics approach: Caspian terns and juvenile salmonids in the Columbia River estuary

Abstract: We estimated the consumption of juvenile salmonids (Oncorhynchus spp.) and other forage fishes by Caspian terns (Sterna caspia) nesting on Rice Island in the Columbia River estuary in 1997 and 1998 using a bioenergetics modeling approach. The study was prompted by concern that Caspian tern predation might be a substantial source of mortality to out-migrating juvenile salmonids from throughout the Columbia River basin, many populations of which are listed as threatened or endangered under the U.S. Endangered Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 41 publications
3
138
4
Order By: Relevance
“…In the Columbia, linked trophic and population models have been essential in understanding the scope of predation by northern pikeminnow (Ptychocheilus oregonensis) and nonnative predators in the mainstem river reservoirs (59)(60)(61)(62), impacts of predation by gulls (Larus spp.) and Caspian terns (Hydroprogne caspia) on migrating juvenile salmon (63)(64)(65)(66), impacts of nonnative mysids and lake trout on kokanee and native salmonids in lakes (28,67), complex species interactions (68), and stage-specific growth and survival of some juvenile salmon populations during freshwater and early marine rearing (69,70). General statistical and population models have been used to explore density dependence and carrying capacities in lakeand stream-rearing populations (71)(72)(73)(74).…”
Section: Incorporating a Food Web Perspective Into Managementmentioning
confidence: 99%
“…In the Columbia, linked trophic and population models have been essential in understanding the scope of predation by northern pikeminnow (Ptychocheilus oregonensis) and nonnative predators in the mainstem river reservoirs (59)(60)(61)(62), impacts of predation by gulls (Larus spp.) and Caspian terns (Hydroprogne caspia) on migrating juvenile salmon (63)(64)(65)(66), impacts of nonnative mysids and lake trout on kokanee and native salmonids in lakes (28,67), complex species interactions (68), and stage-specific growth and survival of some juvenile salmon populations during freshwater and early marine rearing (69,70). General statistical and population models have been used to explore density dependence and carrying capacities in lakeand stream-rearing populations (71)(72)(73)(74).…”
Section: Incorporating a Food Web Perspective Into Managementmentioning
confidence: 99%
“…Avian predation studies have shown a greater susceptibility to terns by hatchery steelhead and yearling Chinook, indicating they have a greater tendency to reside near the surface of the water (Collis et al 2001;Roby et al 2003).…”
Section: Chinook Salmon and Steelheadmentioning
confidence: 99%
“…Diet composition data were not available for all colonies in all years due to funding and logistical constraints. Years when diet composition was evaluated included: 2003and 2008-2009at Brooks Island, 2003at Knight Island, and 2003and 2008-2009 at Eden Landing E-10.…”
Section: Diet Compositionmentioning
confidence: 99%
“…The accuracy of visual identifications was verified using voucher specimens and photographs. We assumed that prey items brought back to the colony by breeding adults were representative of the overall diet of Caspian Terns at that particular colony Roby et al 2003).…”
Section: Diet Compositionmentioning
confidence: 99%
See 1 more Smart Citation